2016
DOI: 10.4103/0973-1296.191459
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of In vitro antibacterial activity and cytotoxicity effect of Nigella sativa oil

Abstract: Background:Methicillin resistance is a serious health concern since it has spread among Staphylococcus aureus and coagulase-negative Staphylococci (CoNS) that are frequent community and nosocomial pathogens worldwide. Methicillin-resistant strains are often resistant to other classes of antibiotics, making their treatment difficult. Nigella sativa oil is known to be active against Gram-positive cocci, yet its in vitro cytotoxicity is rarely investigated, is a proper and powerful candidate for treatment of meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 26 publications
4
32
1
Order By: Relevance
“…8 In recent years, both seeds and its oil have been widely investigated and reported to exhibit several pharmacological effects such as analgesic, anti-inflammatory; 9 anticancer, 10 antiulcer 11 and antibacterial activity. 12 Ugur et al 13 (MICs) showed that N. sativa oil has an excellent antibacterial activity against clinical isolates of methicillin-resistant S. aureus and methicillin-resistant coagulase-negative Staphylococci with very low MIC range of <0.25-1.0 µg/ml. 13 Other…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In recent years, both seeds and its oil have been widely investigated and reported to exhibit several pharmacological effects such as analgesic, anti-inflammatory; 9 anticancer, 10 antiulcer 11 and antibacterial activity. 12 Ugur et al 13 (MICs) showed that N. sativa oil has an excellent antibacterial activity against clinical isolates of methicillin-resistant S. aureus and methicillin-resistant coagulase-negative Staphylococci with very low MIC range of <0.25-1.0 µg/ml. 13 Other…”
Section: Introductionmentioning
confidence: 99%
“…12 Ugur et al 13 (MICs) showed that N. sativa oil has an excellent antibacterial activity against clinical isolates of methicillin-resistant S. aureus and methicillin-resistant coagulase-negative Staphylococci with very low MIC range of <0.25-1.0 µg/ml. 13 Other…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study demonstrated that various pathogenic bacteria, including Streptococcus pneumoniae, one of the most common causes of bacterial tonsillopharyingitis, were sensitive to the combined P. niruri-N. sativa extract. The antibacterial potency of the P. niruri-N. sativa extract was much greater than that of either extract alone, suggesting that both extracts given in combination deliver a synergistic antibacterial effect [82][83][84][85]. The clinical benefit of the combination of P. niruri-N. sativa for the treatment of acute tonsillopharyngitis as confirmed through this study may contribute to minimizing the irrational and excessive use of antibiotics in such an infection, which is mostly viral in origin, thus in turn, the incidence of antibiotic-resistance will hopefully be reduced.…”
Section: Tonsillopharyngitismentioning
confidence: 99%
“…Ugur, Dagi, Ozturk, Tekin, and Findik () determined the MIC values of N. sativa oil against clinical isolates of Staphylococci, including methicillin‐resistant and coagulase‐negative strains, to be between <0.25 and 1.0 μg/ml. The MIC of E. faecalis ATCC 29212, E. coli ATCC 25922, and P. aeruginosa ATCC 27853 standard strains were 2 and 64 μg/ml, respectively.…”
Section: Discussionmentioning
confidence: 99%